2000
DOI: 10.2169/internalmedicine.39.720
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of the Harmful Effects of Smoking and Views on Smoking Cessation Intervention among Japanese Medical Students.

Abstract: Objective To clarify attitudes toward smoking, and views on smokingintervention amongmedical students, as well as to teach them the harmful effects of smoking. Subjects and MethodsWecarried out an anonymous questionnaire among 2nd and 5th year Japanese medical students and 1,137 of them responded. Results Smoking prevalence was 25.1% in men and 8.8% in women in the 2nd year and 43.1% and 9.3%, respectively, in the 5th year. Most respondents thought smoking is harmful to health, but smokers were more likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…As of 2012, COPD was the ninth most common cause of death in Japan, and the study, the number of potential individuals with COPD was reported to be 7. [8][9][10][11][12][13][14][15][16][17][18][19].7% of the population, with an increasing prevalence in association with increasing cigarette consumption and age (7)(8)(9). It is possible to prevent the progression of COPD with early diagnosis and effective treatment (1,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As of 2012, COPD was the ninth most common cause of death in Japan, and the study, the number of potential individuals with COPD was reported to be 7. [8][9][10][11][12][13][14][15][16][17][18][19].7% of the population, with an increasing prevalence in association with increasing cigarette consumption and age (7)(8)(9). It is possible to prevent the progression of COPD with early diagnosis and effective treatment (1,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, people with early signs of COPD often fail to seek medical attention and thus do not receive appropriate treatment in the early stages of the disease (10)(11)(12)(13). Furthermore, although cigarette packages carry warnings of the risk of lung cancer and COPD, data suggest that COPD awareness is lower among people with a history of smoking, particularly current smokers, compared with non-smokers (14,15). Failure to recognize the early symptoms of COPD precludes potential early treatment with improved outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have investigated smoking and its associated factors among medical students, including those that address prevalence, smoking within their families, and attitudes towards antismoking measures. These studies have been conducted in and outside Japan, 59 although no study in Japan has included a representative sample of medical students. Thus, we investigated smoking habits, and factors associated with smoking, in medical students enrolled at randomly selected medical schools across Japan.…”
Section: Introductionmentioning
confidence: 99%
“…According to a study performed by Kawakami, medical students' comprehension of harmful impacts of smoking and their willingness in accomplishing tobacco cessation in the prospect seemed underwhelming (23) We believe that the principal cause for the E-cigarette's popularity is the implementation of a massive advertising blitz appealing to young individuals, like that utilized by conventional cigarette smokers (27,28). Our study's prevalence is considerably larger than that of a study performed among medical students in Poland; nevertheless, it is equivalent to those from USA, where the prevalence was 3.5% and 24.2%, correspondingly (4,29).…”
Section: Discussionmentioning
confidence: 99%